The Prediction Model of Super Large Subsidence in High Water Table Coal Mining Areas Covered with Thick Unconsolidated Layer. (30th March 2021) - Yan, Yueguan; Yan, Weitao; Liu, Jibo; Guo, Junting
Abstract : In mining engineering, after the extraction of underground resources, the maximum surface subsidence is usually less than the mining thickness of coal seam. However, under the condition of thick loose layer, some special phenomena appear in surface subsidence, for example, the maximum surface subsidence value is greater than the mining thickness of coal seam. This special phenomenon cannot be predicted by traditional subsidence prediction methods. To solve this problem, by using the numerical simulation software Fast Lagrangian analysis of continua (Flac), we study the changing rules of subsidence with different strata lithology and unconsolidated layer thickness and reveal the formation mechanism of this law. The results show that the effect of the thick unconsolidated layer on the hard rock is greater than that of the soft rock. When the rock is soft, the unconsolidated layer moves as a whole following the bedrock during the whole mining process. The surface subsidence decreases approximately linearly with the thickness ratio increase of the unconsolidated layer to bedrock. However, when the rock is hard or medium hard, there are supporting structures formed inside the rock stratum, which has supporting effect on the overlying strata. The surface subsidence undergoes three proportional sections, first increases, then decreases, and finally increases with the thickness ratio increase of the unconsolidated layer to bedrock. Combined with these laws, based on the theory that the rock strata space can be completely compressed gradually, we derive the calculation method of surface subsidence under the condition of thick unconsolidated layer and apply it to practice. The results show that the prediction results are consistent with the actual situation and meet the engineering requirements. The research results can provide a reference for the subsidence prediction of similar conditions.